Adolescents sense of identity and its implications for developmentally appropriate interventions for building a safer world through education (2017)
A major concern of educational institutions, families and researchers is the reports from various sources that sizeable numbers of Nigerian adolescents have fragmented, confused, or poorly structured sense of identity which may render them susceptible to external events. Adolescents' sense of identity is therefore, largely unexplored research domain that could benefit from greater attention. This study utilized correlational survey design to examine the pattern of relationship between self-efficacy, parental supports, peer influence, internet usage and sense of identity among adolescents. Two hundred and sixty students (Male=121; Female=139) between 15-18years (x=13.05; SD=14.2) were drawn from secondary schools in Nnewi, Anambra State using simple random sampling technique in four stages. Five standardized self-report questionnaires namely; Serafini and Adams Sense of Identity scale (r=0.78); Jerusalem and Schwarzer General Self Efficacy measure (r=0.76); Pasquali and Araujo Parental Perception Questionnaire (r=0.077); Steinberg and Monahan Resistance to Peer Influence scale (r=0.74) and Young Internet Addiction Test (r=0.79) were used for data collection. Pearson Product Moment correlation result show that while adolescent sense of identity has negative relationship with self-efficacy (r = -.441; p<.05) positive relationship exist with peer influence (r =.253; p<.05). There was no significant relationship with parental supports and internet usage on sense of identity. Multiple regressions analysis revealed that the independent variables contributed 21.0% of the variance in adolescents' sense of identity. Self-efficacy made the most potent (=-409; t (258) =-.6963; P<0.05) contribution in predicting sense of identity. The researcher concluded that for education to contribute significantly towards making the world safer there is urgent need to incorporate enhancement of self efficacy into educational and counselling interventions for in-school adolescents.